DESAIN DAN UJI COBA MODUL KIMIA BERORIENTASI GREEN-CHEMISTRY PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Sepri Weningih; Lisa Utami; Elvi Yenti (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2020)
AbstractThis research aimed at designing Green-Chemistry-oriented Chemistry module on Electrolyte and Nonelectrolyte Solution lesson that was valid based on validity media expert, lesson expert, teacher practicality, and student response. It was Research and Development (R&D) research that implemented Borg and Gall Development model. It was administered at the eleventh-grade students of MIPA 1 of State Senior High School 1 Kampar. The instruments of collecting the data were validity test questionnaire by the experts, teacher practicality test questionnaire, and student response questionnaire. The collected data were analyzed by using Descriptive qualitative and quantitative analysis techniques. The module could be stated appropriate, if it passed validity and practicality aspects. The validity result of chemistry module by 2 media experts and a material expert was 87.09% and it was on very valid category. Practicality test of 3 Chemistry subject teachers showed a result 87.84% that was on very practical category, and it was obtained a very positive response from 10 students, it could be seen from questionnaire result 90.78%. Based on these results, it could be identified that Green-Chemistry-oriented Chemistry module on Electrolyte and Nonelectrolyte Solution lesson was appropriate and practical to be an additional teaching material for teachers at a school.Keywords:Module, Green-Chemistry, Electrolyte and Nonelectrolyte Solution.